Uji Efektivitas Serbuk Daun Mengkudu (Morinda citrifolia L.) dalam Mengendalikan Serangan Nematoda Puru Akar (Meloidogyne spp.) pada Tanaman - Saudah Saudah; Elly Liestiany Liestiany (www.ulm.ac.id, 2026)
Celery is a vegetable with export value which is widely cultivated in the low to highlands but its production is often reduced due to attacks by root knot nematodes (Meloidogyne spp.). Control of these pests generally still relies on chemical pesticides which have the potential to pollute the environment, so environmentally friendly alternatives such as vegetable pesticides are needed. This research aims to examine the effectiveness of noni leaf powder (Morinda citrifolia L.) in suppressing nematode attacks on celery. The design used was a completely randomized design with five treatments and four replications, including noni powder doses of 15, 25, 35 and 45 g. The main parameter is the intensity of the nematode attack. The results showed that noni powder was able to reduce the percentage of attacks from 45% in controls to 16.67%, 10.83%, 6.67% and 4.17% as the dose increased.